Transactions Using E-Wallets: How Is the Perspective of Islamic Economics? - Tira Nur Fitria; Yuwita Ariessa Paravasanti; Iin Emy Prastiwi (Jurnal Ilmiah Ekonomi Islam, 2022)
The development of the digital economy presents a variety of transactions and new financial service products that are increasingly diverse. Doing any transactions by using an E-wallet seems to need to be responded to by an Islamic/Sharia economics view. By looking at the perspective of Islamic economics, we as a society will be able to assess how it plays a role in the development of the digital economy. The purpose of this research is to describe the use of E-wallet in doing transactions based on the perspective of Economics in doing transactions. This research is library research. The result analysis shows that digital wallets are something new in the payment system. The digital wallet in Islamic economics is permissible because it makes it easier for people to transact in daily life when they do not carry cash. In the view of Islam, especially the field of muamalat, it holds the principle of "on" Basically, in terms of muamalat, everything is permissible unless there is a valid argument forbid it". But, people must pay attention to Islamic law when using it. Regarding whether something is illegal or not digital wallets are back at the digital wallet users themselves. Usually, online parties have provided terms and conditions as agreement information with consumers. But, as a Muslim back to the contract and understand the usury value. For that, it would be considered for digital wallet users to understand and read carefully about the terms and conditions in using digital wallets in transactions, so there are no misunderstandings regarding the digital wallet. Therefore, as Muslims, we can use a sharia-based e-wallet to do all transactions as long as it is based on Allah's provisions that do not contain usury, gharar, maysir, tadlis, risywah, and israf. Under certain conditions, digital wallets can be used in an emergency. Payment in cash would also be better if preferred before using the digital wallet in doing any transaction in our daily life.